Changes of South‐Central Pacific Large‐Scale Environment Associated With Hydrometeors‐Radiation‐Circulation Interactions in a Coupled GCM. Issue 17 (9th September 2021) - Li, J.‐L. F.; Xu, Kuan‐Man; Lee, Wei‐Liang; Jiang, J. H.; Fetzer, Eric; Stephens, Graeme; Yu, Jia‐Yuh; Wang, Yi‐Hui
Abstract: A common deficiency in coupled atmosphere‐ocean models is the lack of stratocumulus clouds near the west coasts of continents and shallow cumulus clouds over the trade wind regions. In this study, we examine changes of large‐scale trade wind environment associated with hydrometeors‐radiation‐circulation interactions, focusing over the south‐central Pacific, by carrying out experiments with falling ice (snow) radiative effects (FIREs) on or off using the CESM1‐CAM5 coupled model. Compared to observations/reanalysis data and an experiment with FIREs on (SON), an experiment with FIREs off (NOS) tends to have too‐high (0.3–0.9 K) sea surface temperature (SST) over the eastern half of the Pacific, and weaker surface wind stress over the northeast side but stronger stress over the southwest side of the study domain. The difference between NOS and SON shows lower‐tropospheric wind fields with a cyclonic‐like wind pattern, which is similar to surface wind stress, accompanied with weaker subsidence over the northeast side. The cyclonic‐like wind pattern causes stronger moisture convergence, accompanied with horizontal warm and moist advections, and stronger effective ascending motion over the northeast side of the study domain, building large‐scale environmental conditions to facilitate middle‐ and high‐clouds instead of shallow cumulus clouds in nature. This large‐scale environment in conjunction with the higher SSTs may be also responsible for the lack of the stratocumulus clouds near the coast of America. Remaining biases in SON such as the double intertropical convergence zone and parameterization deficiencies may also prevent a more realistic simulation of trade wind clouds and their associated large‐scale environments. Plain Language Summary: It has been reported that current coupled general circulation models (GCMs) show biases in large‐scale environments, for example, too‐weak subsidence, too‐warm SSTs and too‐weak surface wind stress and trade‐winds, along with too‐few low‐level clouds but with too‐frequent mid‐ and high‐level clouds over the Pacific trade‐wind regions in the Coupled Model Intercomparison Project Phase 5 (CMIP5). This study examined changes of the trade‐wind environment over South Pacific in CESM1‐CAM5 by turning on and off falling ice radiative effects (FIREs). We found that without falling ice radiative effects, that is the case for most CMIP5 models, ascent, warm and moist horizontal advections, and moisture convergence facilitate the occurrence of mid‐ and high‐clouds over trade‐wind regions relative to that with falling ice radiative effects. With falling ice radiative effects on, CESM1‐CAM5 reduced biases in sea surface temperature, winds, surface wind stress, temperature advection and moisture advection/convergence conduce to lower clouds. Key Points: Changes of the trade‐wind environment over South Pacific in CESM1‐CAM5 due to falling ice radiative effects (FIREs) on and off are examined With FIREs off, horizontal warm and moist horizontal advections, and moisture convergence facilitate the occurrence of mid and high clouds With FIREs, reduced biases in sea surface temperature (SST), winds, wind stress, temperature and moisture advections, and moisture convergence conduce to lower clouds